Determining the impacts of residential lakeshore development and various physical factors on largemouth bass (Micropterus salmoides) growth rates - Guarascio, Matthew J. (My University, 2007)
Development of residential lakeshore properties can have several effects on aquatic ecosystems including the thinning of littoral coarse woody habitat. Previous studies have shown that reduction of littoral coarse woody habitat negatively affects largemouth bass (Micropterus salmoides) growth rates. In order to validate these results and attempt to find the mechanism through which bass growth rates are reduced, we surveyed 16 lakes in Vilas, County Wisconsin on a gradient of conductivity and development. Regressions of size-specific growth rates with lake area (p < .01) and maximum depth (p < .05) were negatively correlated and significant. A negative correlation was observed between mean largemouth bass (Micropterus salmoides) growth rate and development, between lake categories of low development low conductivity and high development high conductivity, although this trend was not statistically significant. Our research confirms that extensive residential lakeshore development may reduce the growth rates of bass as demonstrated by Schindler (2000).
21 p.
Keywords: Biology; Zoology